The use of kinematic photogrammetry and LiDAR for reconstruction of a unique object with extreme topography: a case study of Dutchman’s Cap, Baltic seacoast, Lithuania - Ruzgienė, Birutė; Kuklienė, Lina; Kuklys, Indrius; Jankauskienė, Dainora; Lousada, Sérgio (Frontiers in Remote Sensing, 2025)
Nowadays, the development of Unmanned Aerial Vehicle in conjunction with Photogrammetry and LiDAR technologies, has revolutionized the collection of geospatial data. These technologies enable the acquisition of very high-resolution images and dense point clouds. They also allow the generation of aerial mapping products and simulations of geospatial data for territories that are difficult to access using traditional surveying methods. The paper deals with the use of kinematic remote sensing technique for the study of surface with extreme topography as is a near-vertical cliff named Olandian hat situated in the Seaside regional park on the Baltic sea coast of Lithuania. This area has been significantly eroded by the sea due to the climatic changes of the last few decades, which have caused substantial damage to the coastline. Quantitative measurements show that coastal erosion has led to a retreat of up to [X] meters over the last [Y] years. In order to preserve this unique cultural object, needs to keep an observation on a regular basis (as monitoring) for capture the real situation. Applying an appropriate way for generation of the reliable and accurate spatial models of surface with extreme topography, four data sets were processed: images gained with the camera, oriented horizontally; images gained with the camera tilted at about 50°; combining both image sets collected from camera; LiDAR data. Point clouds and orthophoto maps were generated. The evaluation of aerial mapping products showed that the best accuracy was achieved with products derived from the combined image sets, based on the metric of RMSE, with a mean RMSE of 0.048 m in X, Y, and Z directions. The spatial model generated from LiDAR data is more accurate in Z direction. Correct representation of DEM was not possible using only image data from camera horizontally oriented.